The Comprehensive AOCMF Classification System: Condylar Process Fractures - Level 3 Tutorial. Issue 1 (December 2014) - Neff, Andreas; Cornelius, Carl-Peter; Rasse, Michael; Torre, DanielDalla; Audigé, Laurent
This tutorial outlines the detailed system for fractures of the condylar process at the precision level 3 and is organized in a sequence of sections dealing with the description of the classification system within topographical subdivisions along with rules for fracture coding and a series of case examples with clinical imaging. Basically, the condylar process comprises three fracture levels and is subdivided into the head region, the condylar neck, and the condylar base. Fractures of the condylar head show typical fracture lines either within the lateral pole zone, which may lead to loss of vertical height, or medially to the pole zone, with the latter ones usually not compromising the vertical condyle to fossa relation. In condylar head fractures, the morphology is further described by the presence of minor or major fragmentation, the vertical apposition of fragments at the plane of the head fracture, the displacement of the condylar head with regard to the fossa including a potential distortion of the condylar head congruency resulting in dystopic condyle to fossa relations and the presence or absence of a loss of vertical ramus height. A specific vertical fracture pattern extending from the head to the neck or base subregion is considered. Fractures of the condylar neck and base can be differentiated according to a newly introduced one-third to two-thirds rule with regard to the proportion of the fracture line above and below the level of the sigmoid notch, which is presented in the classification article, and are basically subdivided according to the presence or absence of displacement or dislocation. In both condylar neck and base fractures, the classification is again based on the above mentioned parameters such as fragmentation, displacement of the condylar head with regard to the fossa, including dystopic condyle to fossa relations and loss of vertical ramus height, that is, according to the measurement of the condylar process. In addition, the classification assesses a sideward displacement including the respective displacement sector at the neck or base fracture site as well as the angulation of the superior main fragment and also considers a potential displacement of the caudal fragment with regard to the fossa, which may occur in fractures affecting additional fracture locations in the mandible. The design of this classification is discussed along with a review of existing classification systems. The condylar process for fracture location was defined according to the level 2 system presented in a previous tutorial in this special issue.